The Effect of Fomo And The Principle of Qana’ah on The Panic Buying Behavior of Gen Z During Flash Sales of Fashion Products on The E-Commerce Platform Shopee - Syakir Jamaluddin; Sarni Sarni; Cahyo Setiadi Ramadhan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The rapid development of digital marketing strategies in e-commerce has increasingly encouraged irrational consumer behavior during flash sales, particularly among Gen Z, who are more familiar with the digital world. This study aims to determine the effects of FOMO and the principle of qana'ah (contentment with what one has)on panic buying behavior in Gen Z during flash sales of fashion products on the e-commerce platform Shopee. The research employed a quantitative method, using primary data collected through questionnaires completed by 250 Gen Z respondents who are active Shopee users. The sampling technique employed was non-probability, purposive sampling, using a Likert scale questionnaire instrument. The data analysis involved validity and reliability tests, classical assumption tests, and multiple linear regression analysis with a focus on partial tests (t-tests). The data analysis was carried out using the Statistic Product and Service Solution (SPSS) software, version 25. The results show that (1) FOMO partially has a positive and significant effect on panic buying behavior; and (2) the principle of qana'ah partially does not have a significant effect on panic buying behavior.